Ambush - Patterson, James, 1947-; Born, James O.; Patterson, James, 1947- (New York : Little, Brown and Company, 2018)
c
Includes bonus story: Manhunt.
Includes bonus story: Manhunt. This story (c2017) was previously published separately as a BookShots story. It was subsequently published in the compilation Triple homicide : thrillers, with four other Patterson BookShots titles.
Keywords: Bennett, Michael -- (Fictitious character) -- Fiction; Vendetta -- Fiction; Detective and mystery stories; Assassins -- Fiction; New York (N.Y.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction